96.2k views
2 votes
Write an equation for the graph below.

Write an equation for the graph below.-example-1
User Artheyn
by
4.9k points

1 Answer

3 votes

Answer:


f(x)= 3({2})^(x) - 3

Explanation:

Let the equation be of the form


f(x)= a {b}^(x) + k

be the equation, where k=-3 is the horizontal asymptote.

The equation now becomes:


f(x)= a {b}^(x) - 3The curve passes through (0,0)


0= a {b}^(0) - 3


0 = a - 3

a=3

This implies that:


f(x)= 3{b}^(x) - 3

We again substitute (1,3)


3=3{b}^(1) - 3


3b = 6


b = 2

The required equation is


f(x)= 3({2})^(x) - 3

User Quenton
by
4.0k points